Considerations for the assessment of suicidal ideation and behavior in older adults with cognitive decline and dementia. Issue 1 (23rd February 2016) - Alphs, Larry; Brashear, H. Robert; Chappell, Phillip; Conwell, Yeates; Dubrava, Sarah; Khin, Ni A.; Kozauer, Nicholas; Hartley, Dean M.; Miller, David S.; Schindler, Rachel J.; Siemers, Eric R.; Stewart, Michelle; et al.
Abstract: Introduction: Better understanding of suicide risk and its management in older adults with cognitive impairment and/or dementia remain significant unmet public health needs. Urgency to address them derives from concern that CNS treatments for dementia may impact suicide risk. Regulatory guidances requiring assessment of emergent suicidal ideation and behavior (SI/SB) at every clinical trial visit emphasize the need for understanding their prevalence. Methods: The literature regarding SI/SB in older persons with cognitive impairment or dementia was reviewed by an Alzheimer's Association Taskforce with emphasis on epidemiology, classification, assessment, and regulatory requirements. Results: Gaps in our knowledge were identified, challenges discussed and recommendations for future work provided. Discussion: Currently available SI/SB data from geriatric persons with dementia do not provide adequate understanding of its epidemiology, identification, assessment, or management. The growing public health burden of this population requires greater attention from clinicians and researchers on tactics and assessment tools to meet these needs.